Differentiation / Aishah Mahat, Wan Mohamad Dzulfekar Irfan Wan Mohd Dzulkarnain and Muhammad Faiz Adzeem Mohd Fadly - Mahat, Aishah; Wan Mohd Dzulkarnain, Wan Mohamad Dzulfekar Irfan; Mohd Fadly, Muhammad Faiz Adzeem (UiTM Cawangan Johor Kampus Pasir Gudang, 2024)
This e-book, Differentiation, aimed to help students in mathematics. Our target audience for this module are students who take foundation courses. This e-book includes many examples of varying types of questions on the topic of differentiation, which would help students to become more familiar with differentiation questions. Furthermore, solutions for these questions are provided, which would also help students learn how to solve familiar questions.